Socioeconomic inequality in Viet Nam - Cuong Viet Nguyen; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study provides an introduction to major discussions and core findings on inequalities in Viet Nam, drawing on a review of recent research, consideration of how inequality is discussed in legal documents, and an analysis of inequality using household survey data from Viet Nam. Inequality is widely mentioned in legal documents. As of May 2024, there are 443 legal documents that mention the term 'gap between the poor and the rich' and 2,200 legal documents mentioning the term 'social equity'. The term 'gender equality' is mentioned in 6,744 legal documents. Regarding academic studies, most focus on expenditure and income inequality using household surveys. Using VHLSS data, we measure inequality in different welfare indicators, including consumption expenditure, income, electricity spending, and durable and housing value. Although relative inequality remained stable from 2010 to 2022, absolute inequality, as measured by the absolute Gini coefficient, increased, indicating a widening absolute gap in living standards between the poor and the rich.
Keywords: O10; D63; D31; 330; inequality; social equity; income distribution; Gini index; Viet Nam